2022
DOI: 10.1007/s10707-021-00460-z
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of twitter as a relevant human mobility proxy

Abstract: During the last years, the analysis of spatio-temporal data extracted from Online Social Networks (OSNs) has become a prominent course of action within the human-mobility mining discipline. Due to the noisy and sparse nature of these data, an important effort has been done on validating these platforms as suitable mobility proxies. However, such a validation has been usually based on the computation of certain features from the raw spatiotemporal trajectories extracted from OSN documents. Hence, there is a sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…As previously mentioned, human mobility exhibits different characteristics at different scales 42 . In recent work, it has been shown that the granularity in which mobility is analyzed using digital data captures does capture some of the structural differences across scales 40 . Our research group’s work on studying these differences across scales is ongoing 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, human mobility exhibits different characteristics at different scales 42 . In recent work, it has been shown that the granularity in which mobility is analyzed using digital data captures does capture some of the structural differences across scales 40 . Our research group’s work on studying these differences across scales is ongoing 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the data can help refine interventions by providing near real-time information about changes in patterns of human movement, which can inform policy and messaging around social distancing and other interventions. Specific applications using many of the aforementioned data sources, from social networks 40 to cellphone location data 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Being able to know the path followed is becoming relevant to understand human mobility and consequently developing possible alternatives. Over the years, to overcome the limitation just mentioned various models able to perform path and short-term prediction have been developed [8][9][10][11][12][13][14]. Thanks to these models, it is possible first to identify the path of the users and then to integrate new types of data into mobility studies, generating more accurate and detailed OD matrices from a spatial and temporal perspective [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In general, mobility is affected by global long-term events such as economic crises [15][16][17] and conflicts 18 , and by local short-term events like social unrest and extreme natural events [19][20][21][22] . Mobility data are also used to better assess exposure to health-threatening phenomena 23 .Smartphone mobility data play a key role in estimating mobility patterns [24][25][26][27][28][29][30] . Apple's Mobility Trends Reports and Google's Community Mobility Reports were two global data sets made available to researchers during COVID-19 pandemic [31][32][33][34][35] .…”
mentioning
confidence: 99%
“…Smartphone mobility data play a key role in estimating mobility patterns [24][25][26][27][28][29][30] . Apple's Mobility Trends Reports and Google's Community Mobility Reports were two global data sets made available to researchers during COVID-19 pandemic [31][32][33][34][35] .…”
mentioning
confidence: 99%